Analysis of zero balance and dormant project of customer experience department of BRAC Bank Limited - Trisha, Tasnuva Tabassum (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2015.